The Impact of the Project Pedagogy Strategy to Developing Some Biomotor Abilities and Learning Some Artistic Gymnastics Skills For Students - Ola Salam Ghazi; Huda Abdulsamee Abdul Wahhab (Institute of Medico-legal Publications Pvt Ltd, 2021)
The researchers used the experimental design, as for the research community, the third-year students in theCollege of Physical Education and Sports Sciences at the University of Kufa for the academic year 2020-2021, whose number is (56) students, then a sample consisting of (20) students was selected in order toapply the main experiment on it according to the experimental design of one group, then tests of biomotorabilities and artistic gymnastics skills were applied to them, and appropriate statistical treatments were usedto reach the results, after which the results were presented, analyzed and discussed, and he reached thefollowing: The use of exercises according to the pedagogy strategy of the project has a positive effect ondeveloping some biomechanical abilities and learning some artistic gymnastics skills for students. The useof exercises according to the pedagogy strategy of the project is better than the method used, which increasedthe development of some biomechanical abilities and learned some technical gymnastics skills for students.